MOBILE WEB-BASED ACADEMIC SERVICE INFORMATION SYSTEM FOR IMPROVING EDUCATIONAL SERVICES AND QUALITY AT MTS MATHLAUL ANWAR TALANGPADANG TANGGAMUS - Khoirum Mustofa; Siti Mukodimah; Riki Renaldo (YHMM PUBLISHING, 2025)
The development of information technology in education encourages schools to improve the quality of academic services through effective and accessible digital systems. MTs Mathlaul Anwar Talangpadang Tanggamus still faces challenges in managing academic services manually, including grade processing, attendance management, class scheduling, and payment information, resulting in delays and ineffective services for students and parents. This study aims to design and implement a mobile web-based Academic Service Information System to improve the efficiency and quality of academic services. The research applied the Waterfall method consisting of requirement analysis, system design, implementation, testing, and maintenance stages. Data collection techniques included observation, interviews, and literature studies. System testing using the Blackbox Testing method on seven main menus showed that all features functioned properly without errors. Quantitative analysis involved 58 respondents consisting of 26 eighth-grade students and 32 ninth-grade students, resulting in an average system success rate of 93.7%. The results indicate that the developed system successfully simplifies academic management, accelerates information access, and enables parents to monitor students’ academic progress in real-time through mobile devices.